Acceptance of public cloud storage services in South Korea: A multi-group analysis. (April 2020) - Song, Chi-hoon; Kim, Sang Woo; Sohn, Young-woo
Highlights: This study explored the differences and and similarities between users and nonusers in the context of public cloud storage services. For social influence, there was a significant difference between users and nonusers. For users, social influence was not a determinant for positive intention to use PCSS, whereas it was a determinant for nonusers. For other factors, there were no significant differences between the two groups, but each showed meaningful similarities. Habit was the strongest predictor of the intention to use for both users and nonusers, whereas hedonic motivation was not an important concern for both. Performance expectancy was a determinant for positive intention to use PCSS for both groups. Effort expectancy was a determinant for positive intention to use PCSS for users, whereas it was not a determinant for nonusers. Abstract: As cloud computing has spread from the enterprise sector to individuals, there has been a growing need for research on the adoption of cloud computing at the individual level. However, relatively little research has investigated the differences and similarities between users and nonusers regarding the individual-level technology acceptance. To fill this gap, this study explored the differences and similarities between users and nonusers in the context of public cloud storage services of South Korea. Data (users = 210; nonusers = 187) were analyzed using structural equation modeling. For social influence, there was a significant difference between users and nonusers. For users, social influence was not a determinant for positive intention to use PCSS, whereas it was a determinant for nonusers. For other factors, there were no significant differences between the two groups, but each showed meaningful similarities: habit was the strongest predictor of the intention to use for both users and nonusers, whereas hedonic motivation was not an important concern for both; performance expectancy was a determinant for positive intention to use PCSS for both groups. Effort expectancy was a determinant for positive intention to use PCSS for users, whereas it was not a determinant for nonusers. These results can provide academic researchers and businesses with insights into individual-level adoption of cloud computing.